Inability to perform 'en bloc' pulmonary vein isolation requiring ablation of the intervenous carina increases recurrence of atrial fibrillation: A meta‐analysis. Issue 12 (9th November 2022) - Vamos, Mate; Saghy, Laszlo; Jankelson, Lior; Garber, Leonid; Pap, Robert
Abstract: Introduction: Failure to isolate ipsilateral pulmonary veins (PV) "en bloc" by wide‐area circumferential ablation (WACA) may necessitate ablation at the intervenous carina. It is unknown how this scenario impacts rates of atrial fibrillation (AF) recurrence. Methods: A standard random‐effect meta‐analysis of randomized or observational studies were performed, where the outcome of first‐time AF ablation was reported in patients with "en bloc" isolation of PVs by WACA as compared with those in whom ablation at the intervenous carina was needed after WACA to achieve complete isolation. Results: A total of five single‐center, observational studies (N = 1185) and one, multi‐center randomized trial (N = 234) were enrolled. PV isolation could be achieved by WACA "en bloc" in 902/1419 (63.6%) cases. The rest required additional ablation at one or both of the left and right intervenous carinas to achieve isolation. The follow‐up time after ablation ranged from 1 to 2 years in the included trials. The incidence of AF recurrence proved to be significantly lower in patients with successful "en bloc" isolation compared to those requiring carina ablation(s) to achieve complete bilateral PV isolation (MH‐OR 1.89, 95% CI 1.42–2.53, p < .01) Conclusion: This present meta‐analysis demonstrates a lower arrhythmia recurrence rate in patients with bilateral "en bloc" isolation, as compared to those who needed additional carina ablation for complete PVI. Therefore, it is imperative that every effort be made to isolate ipsilateral PVs "en bloc" during PVI.